A family history of fracture and fracture risk: a meta-analysis. - Kanis, J; Johansson, H; Oden, A; Johnell, O; De Laet, C; Eisman, J; McCloskey, E; Mellstrom, D; Melton, L; Pols, H; Reeve, J; Silman, A; et al. (2004)
The aims of the present study were to determine whether a parental history of any fracture or hip fracture specifically are significant risk factors for future fracture in an international setting, and to explore the effects of age, sex and bone mineral density (BMD) on this risk. We studied 34,928 men and women from seven prospectively studied cohorts followed for 134,374 person-years. The cohorts comprised the EPOS/EVOS study, CaMos, the Rotterdam Study, DOES and cohorts at Sheffield, Rochester and Gothenburg. The effect of family history of osteoporotic fracture or of hip fracture in first-degree relatives, BMD and age on all clinical fracture, osteoporotic fracture and hip fracture risk alone was examined using Poisson regression in each cohort and for each sex. The results of the different studies were merged from the weighted beta coefficients. A parental history of fracture was associated with a modest but significantly increased risk of any fracture, osteoporotic fracture and hip fracture in men and women combined. The risk ratio (RR) for any fracture was 1.17 (95% CI=1.07-1.28), for any osteoporotic fracture was 1.18 (95% CI=1.06-1.31), and for hip fracture was 1.49 (95% CI=1.17-1.89). The risk ratio was higher at younger ages but not significantly so. No significant difference in risk was seen between men and women with a parental history for any fracture (RR=1.17 and 1.17, respectively) or for an osteoporotic fracture (RR=1.17 and 1.18, respectively). For hip fracture, the risk ratios were somewhat higher, but not significantly higher, in men than in women (RR=2.02 and 1.38, respectively). A family history of hip fracture in parents was associated with a significant risk both of all osteoporotic fracture (RR 1.54; 95CI=1.25-1.88) and of hip fracture (RR=2.27; 95% CI=1.47-3.49). The risk was not significantly changed when BMD was added to the model. We conclude that a parental history of fracture (particularly a family history of hip fracture) confers an increased risk of fracture that is independent of BMD. Its identification on an international basis supports the use of this risk factor in case-finding strategies.